2009
DOI: 10.1063/1.3174914
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic-enhanced polymer photovoltaic devices incorporating solution-processable metal nanoparticles

Abstract: We have explored the effect of gold nanoparticle ͑Au NP͒-induced surface plasmons on the performance of organic photovoltaic devices ͑OPVs͒. The power conversion efficiency of these OPVs was improved after blending the Au NPs into the anodic buffer layer. The addition of Au NPs increased the rate of exciton generation and the probability of exciton dissociation, thereby enhancing the short-circuit current density and the fill factor. We attribute the improvement in device performance to the local enhancement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
172
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 289 publications
(183 citation statements)
references
References 24 publications
6
172
2
1
Order By: Relevance
“…7b the increase in the EQE via incorporating the 15% Au NRs in ABL solution. We found that the EQE was enhanced by up to 12-14% respectively around 520-640 nm, which are near to the transverse absorption reported results similar to ours with the EQE curves for both reference and NPs devices having the same absorption ranges with a slight enhancement in the tail near the IR region [4,11,15].…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…7b the increase in the EQE via incorporating the 15% Au NRs in ABL solution. We found that the EQE was enhanced by up to 12-14% respectively around 520-640 nm, which are near to the transverse absorption reported results similar to ours with the EQE curves for both reference and NPs devices having the same absorption ranges with a slight enhancement in the tail near the IR region [4,11,15].…”
Section: Resultssupporting
confidence: 88%
“…For these devices, we observed a clear enhancement in the Jsc from 6.6 to 7.7 mA/cm 2 , which lead to 21.3% enhancement in the PCE. We found such enhancement quite interesting considering the low density of the MNPs in the layer as compared to some reported studies in which the density of the particles was much higher [9,11,15]. The density of the NRs embedded in the ABL of our samples was estimated from the SEM as ~ 6 -8 × 10 8 rods/cm 2 .…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations